2020
DOI: 10.1093/advances/nmz065
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research on the Health Benefits of Blueberries and Their Anthocyanins

Abstract: Awareness of the human health benefits of blueberries is underpinned by a growing body of positive scientific evidence from human observational and clinical research, plus mechanistic research using animal and in vitro models. Blueberries contain a large number of phytochemicals, including abundant anthocyanin pigments. Of their various phytochemicals, anthocyanins probably make the greatest impact on blueberry health functionality. Epidemiological studies associate regular, moderate intake of blueberries and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
248
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(256 citation statements)
references
References 191 publications
(228 reference statements)
4
248
0
4
Order By: Relevance
“…Compared to the peels of other fruits with similar colour (red), the concentration of total anthocyanins was evidently higher in tamarillo. For example, the peels of red grape, red plum and red apple had the total anthocyanin concentrations of 27, 20 and 12 mg/100 g FW, respectively (approximately equal to 138.75, 156.62 and 83.1 mg/100 g DW, respectively) [20]. Total anthocyanin content in pulp of Mulligan, Laird's Large and Amber was much higher than its counterpart (peel), with 486.84, 481.37, and 29.70 mg/100 g DW, respectively.…”
Section: Anthocyanin Compound Profilesmentioning
confidence: 99%
“…Compared to the peels of other fruits with similar colour (red), the concentration of total anthocyanins was evidently higher in tamarillo. For example, the peels of red grape, red plum and red apple had the total anthocyanin concentrations of 27, 20 and 12 mg/100 g FW, respectively (approximately equal to 138.75, 156.62 and 83.1 mg/100 g DW, respectively) [20]. Total anthocyanin content in pulp of Mulligan, Laird's Large and Amber was much higher than its counterpart (peel), with 486.84, 481.37, and 29.70 mg/100 g DW, respectively.…”
Section: Anthocyanin Compound Profilesmentioning
confidence: 99%
“…Blueberry ( Vaccinium spp.) is the second most important soft fruit after strawberry, and it has also been popularized as a ‘superfood’ as a result of the multiple health benefits conferred by its abundant polyphenolic content (Kalt et al , ). A previous psychophysical study indicated that consumers prefer sweet berries with intense flavor (Gilbert et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing nutritional interventions using different types of fruits such as blueberry [ 8 ], strawberry [ 46 ], and passion fruit peel extract [ 48 ] promoted a significant reduction in pain in individuals with osteoarthritis. This result is possibly attributed to the content of polyphenols present in blueberry and strawberries and flavonoids present in the passion fruit peel extract, which have anti-inflammatory effects, besides promoting anabolic effects in the cartilage, possibly explaining their activity against pain [ 57 ].…”
Section: Discussionmentioning
confidence: 99%